Chiral inversion and enhanced cooperative self-assembly of biosurfactant-functionalized porphyrin chromophores. Issue 14 (4th March 2020) - Peters, Kyle C.; Mekala, Shekar; Gross, Richard A.; Singer, Kenneth D.
Abstract : A newly synthesized sophorolipid–(Zn)porphyrin (short lipid chain) exhibits chiral inversion and enhanced cooperative self-assembly compared to its analogue long-chain compound. Abstract : A new self-assembling di-conjugated sophorolipid–(Zn)porphyrin was synthesized with a short lipid chain length connecting the porphyrin and disaccharide moieties in order to influence the self-assembled state. In dilute solution, circular dichroism measurements of the ordered molecules exhibited Cotton effects indicative of right-handed exciton-coupling; a chirality inversion compared to our previous report on (long-chain) sophorolipid–(Zn)porphyrins that formed a left-handed system. The self-assembly process was investigated by variable-temperature CD. Cooling curve profiles exhibited simultaneous evolution of net helicity and aggregation that corresponds with the cooperative assembly model. Analysis revealed a 3-fold increase in enthalpy of polymerization compared to long-chain species implying that shortening the distance between porphyrin and disaccharide moieties enhance the cooperative self-assembly. The morphology of assembled aggregates was examined by electron microscopy and showed mesoscopic cup-staked structures and nanofibrils.